2021
DOI: 10.54855/ijte2202011
|View full text |Cite
|
Sign up to set email alerts
|

The Opinions and Perceptions of K1-3 Parents in Relation to BYOD Implementation in Japanese Kindergartens

Abstract: Bring Your Own Device (BYOD) is a concept that is gaining a following worldwide as a cost-effective means for schools to provide 21st-century skills (Bell, 2010) with limited funding. The current paper shows the results of a survey into the opinions and perceptions of parents of Japanese K1-3 students' use of technology, specifically the application of BYOD at this level. This survey was conducted at a private kindergarten in Japan and was administered to 100 parents of K1-3 students. Results of this survey sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The children's age and gender were the two most considered factors in the reviewed studies. Six studies indicated that parents alter their views on children's technology use based on the child's age (Covolo et al, 2021;Istenič et al, 2023;Kucirkova et al, 2018;Mikelic Preradovic et al, 2016;Vittrup et al, 2016;White, 2022). For instance, (Mikelic Preradovic et al, 2016) found that parents generally negatively perceive digital device use by children aged two or younger.…”
Section: The Factors Related To the Children Themselvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The children's age and gender were the two most considered factors in the reviewed studies. Six studies indicated that parents alter their views on children's technology use based on the child's age (Covolo et al, 2021;Istenič et al, 2023;Kucirkova et al, 2018;Mikelic Preradovic et al, 2016;Vittrup et al, 2016;White, 2022). For instance, (Mikelic Preradovic et al, 2016) found that parents generally negatively perceive digital device use by children aged two or younger.…”
Section: The Factors Related To the Children Themselvesmentioning
confidence: 99%
“…The one factor that garnered the most attention among the reviewed studies was educational level, but studies investigating this factor produced inconsistent findings. (White, 2022) and (Papadakis et al, 2019) demonstrated that parents with higher educational levels were more likely to recognise the potential disadvantages of digital technology and engage in proactive mediation, such as offering alternative play options and restricting screen time for their children. However, (Vittrup et al, 2016) and (Vaiopoulou et al, 2021) found that parental education level did not significantly impact their perceptions, including usability, enjoyment, involvement, learning, worries, and values.…”
Section: The Factors From Parentsmentioning
confidence: 99%